PROCESSING CHARACTERISTICS OF VANAME SHRIMP (Litopenaeus vannamei) PEELED FROZEN RAW Peeled Tail On (PTO) - Maulani, Aghitia; Salampessy, Randi Bokhy Syuliana; Napitupulu, Andrian Agung (Aurelia Journal, 2024)
Shrimp is one of the aquaculture products that contributes greatly to the country's foreign exchange. Vaname shrimp can be used as processed products, one of which is frozen raw peeled shrimp products. The purpose of this study is to determine the characteristics of the Peeled Tail On (PTO) frozen raw peeled shrimp processing process consisting of processing process flows, quality testing, application of temperature, yield, labor productivity, application of basic feasibility, and waste management. Primary data collection is carried out by participating in the production process, observation and conducting interviews with employees. While secondary data is obtained from company archives/documentation. The processing of PTO vaname shrimp goes through 23 stages of the process starting from receiving raw materials to loading. The results of organoleptic quality tests of raw materials and sensory tests of the final product show values between 8-9. Microbiological quality tests on raw materials and products have met the standards. Chemical quality tests on raw materials have met the specified standards. The application of temperature during the process has met the processing temperature standards in the company. The yield and productivity of the workforce have met the company's standards. Sanitation and hygiene have been implemented well, as evidenced by the certificates of Sanitation Standard Operating Procedures (SSOP), Good Manufacturing Practices (GMP), and feasibility of processing. Solid waste in the form of head and skin waste is processed into flour. The resulting liquid waste is treated at the WWTP (Wastewater Treatment Plant).